Stakeholder management practices and education quality: a literature review using content analysis - Yihong Peng; Bity Salwana Alias; Xinyu Wan; Azlin Norhaini Mansor (Intelektual Pustaka Media Utama, 2026)
Stakeholder theory and stakeholder management models’ impact on the quality of education throughout the last ten years is investigated in this systematic literature review (SLR). It gives a summary of recent findings and points out areas that require more research. The preferred reporting items for systematic reviews and meta-analyses (PRISMA) technique was used in the study to search six databases, and 34 papers were chosen for review. Leximancer was used to refine the content analysis. The primary objective is to investigate the relationship between excellent education and efficient stakeholder management. With a detailed literature analysis identifying major themes and prospects for additional research on partnerships and stakeholder views in education, the study underlines the growing acknowledgement of the impact of stakeholder involvement on educational outcomes. Future studies on this subject could significantly raise the standard, effectiveness, and sustainability of global education. Future research could be improved by broadening the search parameters, promoting interdisciplinary work, and stressing stakeholder involvement, despite some constraints including inconsistent methodology and geographic bias.